Study expectations of different domiciled Postgraduate-Taught students in a UK post-1992-institution. Issue 3 (6th July 2015) - Morgan, Michelle
Abstract : Purpose: – The purpose of this paper is to report the notable findings of students with different domiciled status. There is a lack of research and understanding of how prior study experiences and the expectations of new students that are due to embark on an MSc by coursework level (also known as postgraduate-taught [PGT]) can impact on their study and ability to persist and succeed. The research available has mainly been confined to post-experience surveys. By identifying prior study experiences and study expectations, education providers in higher education institutions can use these insights not only to attract more students but to improve retention rates and the overall student experience. The research undertaken in the Faculty of Science, Engineering and Computing at a London-based, post-1992 institution aims to provide valuable data and insights into this nationally and internationally neglected area. Design/methodology/approach: – New taught postgraduate students provided data on their previous study experiences, study expectations, opinions of postgraduate-level study and demographic data via a hard copy questionnaire which was distributed and completed during the orientation period in September 2012. It was entered into the Statistical Package for the Social Sciences (SPSS), and a range of tests were run on the data. Findings: – The findings in this paper and the project in general will be further explored and investigated as a result of the Higher Education Funding Council for England (HEFCE) awarding a major grant to the post-1992 university to undertake research into these areas amongst nine similar English universities. Research limitations/implications: – As the research was conducted over a one-year period, the findings are based on the limitations that such a time and financially limited project can offer. The institution at which the research was undertaken is a post-1992 institution that has high concentration towards teaching functions. The findings in this paper and the project in general will be further explored and investigated as a result of the HEFCE awarding a major grant to the post-1992 university to undertake research into these areas among nine similar English universities. Originality/value: – The research highlights the similarities and differences in prior study experiences and expectations of studying at PGT level between the UK-, the European Union- (EU) and Non-EU-domiciled respondents. The research offers potentially important findings for similar institutions that are currently looking to develop and expand their PGT provision.